This dark night : Emily Brontë, a life - Lutz, Deborah (W.W. Norton & Company, 2026)
"Emily Brontë was only twenty-seven-years old when she started work on one of the most important novels in the English language. In two years, she completed Wuthering Heights in 1847, while the world took almost a hundred years to catch up. It has taken the world even longer to know Brontë-enigmatic, less initially renowned than sister Charlotte of JANE EYRE fame, and with a legacy marred by the loss (and likely destruction) of almost all her personal papers. THIS DARK NIGHT is a portrait of Emily Brontë, her writing sisters, and the material and cultural world they lived in, tracing Brontë's passions from the incomparable moors outside her home to the storm, strife, and longing that populates her poetry and novel. Deborah Lutz reconstructs the texture of Emily's days as masterful writer and woman tending to a household in Victorian England. She places Brontë in the history of modern thought and emerges with a mythic figure: consummate artist, deeply idiosyncratic person, and creator of a cherished and extraordinarily influential work"-- Provided by publisher.